Planeación Financiera a la Compañía de Transporte Pesado Condoy & Ortiz C.A. Condriz, de la parroquia Los Encuentros, cantón Yantzaza, provincia Zamora Chinchipe. Periodos 2022-2026 - Armijos Castillo., Jefferson Anthony (2023)
The Curricular Integration Work entitled: Financial Planning for the Heavy Transport Company Condoy & Ortiz C.A. Condriz, from Los Encuentros parish, Yantzaza canton, Zamora Chinchipe province. Periods 2022-2026, was prepared as a guide to carry out the objectives of the company and its shareholders, taking advantage of resources effectively and maximizing profits for the coming years, through the correct decision-making of its manager. In order to meet the general objective, firstly, the previous visit to the Company Manager was carried out, with the purpose of obtaining information that would help better understand the business context and to develop financial planning. Once the data was extracted, the financial analysis was applied to the financial statements for the year 2021, by applying the indicators established by the Superintendency of Securities and Insurance Companies, it was determined that the company for every dollar it owes in the short term, has $8, 61 to meet its obligations to third parties; The net working capital at the end of the year was $159,292.47, which means that once the short-term liabilities are paid, the company still has sufficient resources to continue operating safely; The turnover of sales indicates that the company's assets rotate 4 times to produce profits, indicating that the assets have a great facility to generate income. A leverage of $1.13 indicates that the company has sufficient solvency to cover all of its assets and that it does not need external financing. The net return on sales is 7%, indicating that it is profitable to buy shares and invest in the company. 4 Then financial planning was developed based on the history of the annual sale, to forecast sales for transportation services, through the judgment method, the percentage increase method, and the company's policies; and, to project expenses, the Consumer Price Index for 2021 was used, which served as the basis for structuring the cash inflow and outflow programs, which allow knowing the capital that the company will have for future operations and investment; Subsequently, the Pro Forma Income Statement and the Pro Forma Statement of Financial Position were prepared, designed based on sales for the year 2021, making it easier to know the expected income and expenses for the period 2022-2026. Next, the development of the break-even point continued, for the forecast period, where it was possible to analyze the profitability that the company could obtain from its sales level, covering its total costs; and finally, to meet the last objective, the financial planning report was prepared, which accurately describes the procedures and formulas used with which financial planning was developed and the proper conclusions reached by the analyst. Once the Curricular Integration Work was completed, it was possible to specify that the correct application of financial planning tools represents a strategic advantage of one company over another, since it anticipates the values that could be generated in the future as a result of previously established actions.